Insights on Controlling Factors of Hydraulically Induced Seismicity in the Duvernay East Shale Basin. (19th February 2021) - Hui, Gang; Chen, Shengnan; Gu, Fei; Pang, Yu; Yu, Xinran; Zhang, Linyang
Abstract: Historically, the Duvernay East Shale Basin had been regarded as a seismicity‐quiescent region. However, an ML 4.18‐magnitude earthquake on 04/03/2019 was triggered due to hydraulic fracturing of two horizontal wells. The physical mechanism and controlling factors of this large‐magnitude earthquake are not well understood. In this work, the coupled modeling of the ML 4.18 case is conducted to quantify the poroelastic effects during fluid injection and to reveal the triggering mechanism of this earthquake cluster. Additional simulations of tested cases with different hydraulic, geomechanical, and operational parameters are also conducted to quantify the effects of these factors on hydraulically induced seismicity. It is found that the hydraulic fractures of two wells propagated within the Duvernay formation and connected with the inferred fault. The increase in pore pressure reduced the shear stress of the fault and caused the fault slip. The hydraulically induced seismicity is susceptible to the low permeable injection layer and high‐permeable fault, less rigid fault with low‐Biot's coefficient, large fluid injection, and proximity of hydraulic fracturing‐fault distance. Enlarging the distance between the stimulated well and seismogenic fault is the first‐order choice to mitigate seismic risks. Under the proximity of well‐fault distance, reducing the fracturing size job would be an effective approach to reduce the expected magnitude of hydraulically induced seismicity. Key Points: Hydraulic connection between the stimulated well and an inferred NE20°‐trending‐fault triggered the ML 4.18 earthquake Induced seismicity is susceptible to hydraulic fracturing (HF)‐fault distance, fault and injection permeability, fault rigidity, and injection rate and volume Enlarging HF‐fault distance and reducing fracturing job size are practical approaches to reduce the potential seismic risks